2015
DOI: 10.1007/s10877-015-9737-0
|View full text |Cite
|
Sign up to set email alerts
|

Variability of FeNO in healthy subjects at 2240 meters above sea level

Abstract: Fraction of exhaled nitric oxide (FeNO) is a marker of eosinophilic airway inflammation. Altitude above sea level can affect measurements of this index, but there is only limited information regarding the diurnal variation (ante meridiem vs. post meridiem) and reproducibility of FeNO on consecutive days at moderate altitudes. To evaluate the diurnal variability of FeNO and assess its reproducibility over five consecutive days in healthy individuals living at 2240 m, and to compare the FeNO readings taken with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The NIOXMINO uses a disposable electrochemical sensor and was developed commercially for use in a clinical setting around the management of airway inflammation and asthma. The main issue with the NIOX MINO system is that it cannot be calibrated, and indeed there has been considerable debate in the literature around the external validity of NIOX MINO measurements, particularly at altitude where only one validation study exists to support use of the device under low barometric pressure conditions (Beall et al, ; Gochicoa‐Rangel et al, ; Hemmingsson et al, ; Laskowski et al, ). From this, it is clear that NIOX MINO measures are not interchangeable with Siever's measures and it is fair to question the validity of the results presented in this article.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NIOXMINO uses a disposable electrochemical sensor and was developed commercially for use in a clinical setting around the management of airway inflammation and asthma. The main issue with the NIOX MINO system is that it cannot be calibrated, and indeed there has been considerable debate in the literature around the external validity of NIOX MINO measurements, particularly at altitude where only one validation study exists to support use of the device under low barometric pressure conditions (Beall et al, ; Gochicoa‐Rangel et al, ; Hemmingsson et al, ; Laskowski et al, ). From this, it is clear that NIOX MINO measures are not interchangeable with Siever's measures and it is fair to question the validity of the results presented in this article.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the device shows high repeatability and use of calibration for the chemiluminescence analyzer (Brody et al, ; Choong & David, ; Olin et al, ; Travers et al, ). Only one validation study supports the use of the NIOX MINO at high altitude (Gochicoa‐Rangel et al, ). The latter study compared the NIOX MINO® to the Sievers NOA 280i® and reported a high correlation (0.96, p < .001) between the two measurement devices (participants were healthy nonsmoking adults of Mexico City, Mexico, measured at an altitude of 2,240 m above sea level).…”
Section: Discussionmentioning
confidence: 99%
“…The current knowledge regarding the diurnal FeNO variability shows its minimal variation. In five subsequent days, the FeNO coefficient of variation (CV) in the morning was 15.4% and 13.6% in the evening in the healthy subjects located at 2240 m above the sea [15]. Other researchers suggest slight FeNO variation with the highest values in the morning and the lowest values in the evening [16].…”
Section: Discussionmentioning
confidence: 90%
“…The 20% of the variability was explained by age, rhinoconjunctivitis, positive skin prick test and removal of cat and/or dog from the house [25]. The internal variability (within the group) of FeNO seems to be stable according to current litera-ture [26,27] and should not impact the differences between the status of children.…”
Section: Discussionmentioning
confidence: 99%